SETTLEMENTS IN THE RUCĂR – BRAN CORRIDOR. DYNAMICS OF FUNCTIONAL TYPES - LUCIAN DAVID (Revue Roumaine de Géographie)
The village is a synthesis of demographic, territorial and functional components, in which the functions highlight the connection between the demographic and the territorial structure. In order to assess the function (or functions) of a rural center, first one must get to know and compare the types of activities. The basic criteria for identifying the types of activity are the professional structure of the employed population and the production value. Likewise, geographical location is another important factor in defining the economic features. The favourable natural setting, the varied topography, the soil cover, the wealth of vegetal species, the well-developed river system etc., correlated with the existence of extensive pastures and hayfields have encouraged the development of a pastoral civilization in the Rucăr – Bran Corridor, which is well known both at home and abroad.